ROMANSY 18 - Robot Design, Dynamics and Control Proceedings of the Eighteenth CISM-IFToMM Symposium - Schiehlen, Werner; Parenti-Castelli, Vincenzo (CISM International Centre for Mechanical Sciences, Courses and Lectures,, 2010)
The papers in this volume provide a vision of the evolution of the robotics disciplines and indicate new directions in which these disciplines are foreseen to develop. Paper topics include, but are not limited to, novel robot design and robot modules/components, service, education, medical, space, welfare and rescue robots, humanoid robots, bio-robotics, multi-robot, embodied multi-agent systems, challenges in control, modeling, kinematical and dynamical analysis of robotic systems, innovations in sensor systems for robots and perception, and recent advances in robotics. In particular, many contributions on humanoid robots from leading Japanese researchers are included.